2019
DOI: 10.1111/jne.12681
|View full text |Cite
|
Sign up to set email alerts
|

Steroid profiles in quail brain and serum: Sex and regional differences and effects of castration with steroid replacement

Abstract: Both systemic and local production contribute to the concentration of steroids measured in the brain. This idea was originally based on rodent studies and was later extended to other species, including humans and birds. In quail, a widely used model in behavioural neuroendocrinology, it was demonstrated that all enzymes needed to produce sex steroids from cholesterol are expressed and active in the brain, although the actual concentrations of steroids produced were never investigated. We carried out a steroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 90 publications
3
9
0
Order By: Relevance
“…Because the BnST expresses many androgen receptors, 18,61 it is surprising that T and 5α‐DHT levels are low in this region. It is also noteworthy that androstenedione and 5α‐DHT levels are much higher in some regions than in the blood (up to 20‐fold higher), similar to a recent study in quail using gas chromatography‐mass spectrometry 62 . Cyp17a1 (an enzyme that synthesises androstenedione) is expressed in the songbird brain, 63 with high levels in the VMH and low levels in the LS (similar to androstenedione levels observed here).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Because the BnST expresses many androgen receptors, 18,61 it is surprising that T and 5α‐DHT levels are low in this region. It is also noteworthy that androstenedione and 5α‐DHT levels are much higher in some regions than in the blood (up to 20‐fold higher), similar to a recent study in quail using gas chromatography‐mass spectrometry 62 . Cyp17a1 (an enzyme that synthesises androstenedione) is expressed in the songbird brain, 63 with high levels in the VMH and low levels in the LS (similar to androstenedione levels observed here).…”
Section: Discussionsupporting
confidence: 90%
“…It is also noteworthy that androstenedione and 5α-DHT levels are much higher in some regions than in the blood (up to 20-fold higher), similar to a recent study in quail using gas chromatography-mass spectrometry. 62 Cyp17a1 (an enzyme that synthesises androstenedione) is expressed in the songbird brain, 63 with high levels in the VMH and low levels in the LS (similar to androstenedione levels observed here). Thus, we speculate that androstenedione is synthesised locally in the brain.…”
Section: Local Regulation Of Steroids In the Sdmnsupporting
confidence: 73%
“…A testosterone assay without previous separation from 5α-DHT presumably provides reasonably accurate values because 5α-DHT is present in low concentrations in most mammals but in birds another closely related metabolite, 5β-DHT is present in very large concentrations and if an antibody against testosterone cross-reacts just by a few percent, this might provide a completely false evaluation of its concentration. We recently showed that 5β-DHT is approximately 10 times more concentrated than testosterone in the brain of male Japanese quail (Liere et al, 2019). If there is just a small cross reactivity with 5β-DHT of an antibody against testosterone, this might significantly distort the results but suppliers never report cross-reactivity with this steroid.…”
Section: Measuring Concentrations Of Steroids and Other Hormonesmentioning
confidence: 99%
“…The resulting changes in local E 2 concentrations are less clear. A host of studies indicate that brain steroid concentrations are not a direct reflection of concentrations circulating in the blood (In rodents 10 12 ; in quail 13 ) which led to the discovery that the brain itself can synthesize steroids from cholesterol, independent from the supply of systemic precursors, these are the so-called neurosteroids 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%